Reflective and Technology-Integrated Pedagogy for Mathematics Teacher Education - Tobondo, Yuyun Alfasius (PT. Riset Press International, 2025)
This study explores the integration of reflective pedagogy and technology-enhanced instruction in mathematics teacher education. In response to the growing complexity of 21st-century classrooms, teacher preparation programs must equip educators with the capacity for critical self-assessment and technological proficiency. This research adopts a library research approach by systematically reviewing relevant literature from scholarly journals, books, and academic reports. Through thematic analysis, five key findings were identified: (1) reflective practices promote continuous professional development, (2) technology integration increases student engagement and conceptual understanding, (3) the combination of reflection and technology strengthens teachers’ technological pedagogical content knowledge (TPACK), (4) collaborative and reflective professional development enhances instructional implementation, and (5) integration challenges such as lack of confidence and pedagogical alignment require ongoing support. The study concludes that merging reflective pedagogy with technology integration creates a comprehensive framework for preparing adaptive, self-aware, and innovative mathematics educators. This integrated model provides valuable insights for the design of teacher education programs and underscores the need for professional development structures that foster both reflective and technological competencies. Future empirical research is recommended to validate these findings in classroom contexts and to assess their long-term impact on teaching outcomes.